Effectiveness of Stretch Interventions for Children With Neuromuscular Disabilities: Evidence-Based Recommendations. Issue 3 (2016) - Craig, Jason; Hilderman, Courtney; Wilson, Geoffrey; Misovic, Robyn
Abstract : Purpose: To determine whether casting, orthoses, stretching, or supported standing programs are effective in improving or maintaining body functions and structures, activity, or participation in children with neuromuscular disabilities. Methods: A systematic review was conducted using 6 electronic databases to identify Level 1 and 2 studies investigating stretch interventions for children aged 0 to 19 years with neuromuscular disabilities. Interventions were coded using the International Classification of Function and rated with Grading of Recommendation Assessment, Development and Evaluation, the Oxford Levels of Evidence, and the Evidence Alert Traffic Light System. Results: Sixteen studies evaluated the effectiveness of stretch interventions. Low-grade evidence supports casting temporarily increasing ankle range of motion, orthoses improving gait parameters while they are worn, and supported standing programs improving bone mineral density. Conclusion: There is limited evidence suggesting stretch interventions benefit body functions and structures. There is inconclusive evidence to support or refute stretching interventions for preventing contractures or impacting a child's activity or participation. Trial Registration: Prospero CRD42014013807. Abstract : Supplemental Digital Content is Available in the Text.To determine if casting, orthoses, stretching, or supported standing programs are effective in improving or maintaining body functions and structures, activity, or participation in children with neuromuscular disabilities.